Exploring Black civil society perspectives of drug decriminalization reforms in the Baltimore context: a participatory action qualitative study - Natalie Flath; Lawrence Grandpre; Corey Shdaimah; Judith Park; Jordan J. White; Brook Kearley (Critical Public Health)
Drug decriminalization is gaining recognition in academic and policy settings as an intervention to address the increasingly volatile drug crisis and achieve racially equitable drug policy reform in the United States. However, few studies elicit grassroots perspectives of Black communities most affected by legal change. This study explored the perspectives of Black civil society stakeholders on drug decriminalization to inform policy. From 2021 to 2022, racial justice policy advocates and university-based researchers conducted a participatory qualitative study, interviewing twelve key stakeholders a part of culturally responsive, Black-led efforts addressing drug-related harms at the grassroots level in Baltimore City, Maryland. A rapid qualitative analysis revealed that current decriminalization proposals overlook the structural harms of decades of drug criminalization and do not reflect the values that ground communities’ responses to heal and become architects of the solution. Stakeholders recommended the incorporation of financial reparations and investment into a community-led support system that includes Black-owned businesses, harm reduction organizations, and psychospiritual care initiatives. For decriminalization to be effective in urban U.S. contexts, this study emphasizes the need for reforms to be community-led and inclusive of larger U.S. racial justice policy priorities.